Synergistic cytotoxicity and apoptosis induced in human cholangiocarcinoma cell lines by a combined treatment with tumor necrosis factor-alpha (TNF-α) and triptolide - Tasanee Panichakul (2018)
Cholangiocarcinoma is known to be relatively resistant to chemotherapy. One alternative approach is to use a combination of an immunomodulating agent with an anticancer drug. Here we studied the synergistic actions of TNF-α and triptolide (a diterpene epoxide prepared from Tripterygium wilfordii), previously shown to have antitumor activity against hamster cholangiocarcinoma (CCA) cells. Three human CCA cell lines (HuCCA-1, HubCCA-1, KKU-100 cell lines) were subjected to a combined treatment of TNF-α (0.1-10 ng/ml) and triptolide (5-50 ng/ml) for 24 hours in microculture plates. The combination of TNF-α and triptolide had a significantly increased cytotoxic activity over that of triptolide alone (p < 0.05). Under the same conditions, TNF-α by itself was not cytotoxic to these cell lines. Similarly, the combined treatment could also accelerate apoptotic cell death in all three human cholangiocarcinoma cell lines. The combined treatment of TNF-α at 10 ng/ml and triptolide at 50 ng/ml for 6-10 hours achieved a percentage of apoptotic cells shown by DAPI staining of 18-65%, compared to only 6-20% apoptotic cells for triptolide alone. Analyzing the possible mechanisms of the combined treatment, we found by Western blot that at 6 hours, there was a poly (ADP-ribose) polymerase (PARP) cleavage which was not detectable by the treatment of either TNF-α or triptolide alone. The cleavage of PARP was inhibited when the cells were pretreated with the enzyme inhibitor AC-DEVD-CMK, suggesting that apoptosis induced by the combination of TNF-α and triptolide involved activation of caspase 3. These results indicate that apoptosis of human cholangiocarcinoma cell lines as induced by a combination of TNF-α and triptolide is mediated through caspase 3 activation.